Franz Rosenzweig and Karl Barth A Chapter in the Jewish Reception of Dialectical Theology - Herskowitz, Daniel M. 1987- (2017)
The article focuses on the works of theologians Franz Rosenzweig and Karl Barth and discusses the understanding of their works and the reaction to dialectical theology by Jews in 20th century in Weimar Germany. Topics discussed include Rosenzweig's book "Der Stern der Erlösung," Barth's book "Der Römerbrief," and the theological disputes at the time.
Keywords: Barth, Karl, 1886-1968; DER Romerbrief (Book); DER Stern der Erlosung (Book); Dialectical theology; Germany; History; Jews; ROSENZWEIG, Franz, 1886-1929